2002
DOI: 10.2460/ajvr.2002.63.1571
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxytocin treatment in sows on umbilical cord morphology, meconium staining, and neonatal mortality of piglets

Abstract: Oxytocin given to sows at the onset of fetal expulsion significantly increases the rate of fetal distress, anoxia, and intrapartum death in piglets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
6
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 20 publications
2
76
6
3
Order By: Relevance
“…This is emphasized by the finding that over 90% of the intra-partum stillborn piglets are born with a ruptured umbilical cord [17]. Mota-Rojas et al [18] provided indirect evidence for the vital importance of the umbilical cord by demonstrating that administration of oxytocin resulted in a significantly higher percentage of stillbirths with haemorrhage and rupture of the umbilical cord. In piglets born alive but with broken umbilical cords, significantly lower pH values at birth have been found [15].…”
Section: Introductionmentioning
confidence: 92%
“…This is emphasized by the finding that over 90% of the intra-partum stillborn piglets are born with a ruptured umbilical cord [17]. Mota-Rojas et al [18] provided indirect evidence for the vital importance of the umbilical cord by demonstrating that administration of oxytocin resulted in a significantly higher percentage of stillbirths with haemorrhage and rupture of the umbilical cord. In piglets born alive but with broken umbilical cords, significantly lower pH values at birth have been found [15].…”
Section: Introductionmentioning
confidence: 92%
“…The latter were classified according to criteria previously described in detail elsewhere (Mota-Rojas et al, 2002;Mota-Rojas et al, 2005). Briefly, type-I stillbirths occur in the prepartum period whereas type-II stillbirths occur during parturition and they are generally associated with anoxia and dystocia.…”
Section: Methodsmentioning
confidence: 99%
“…It is also being used in more than 80% of swine farms in United States for complementing normal parturition (Straw et al, 2000), probably in attempt to decrease the approximately 5-15% of stillbirths observed in such farms (Leman et al, 1972). However, although administration of oxytocin to parturient sows reduced duration of labor, mortality of the offspring remained unchanged (Randall, 1972;Gilbert, 1999;Mota-Rojas et al, 2002). A critical aspect to be noticed in these studies is that oxytocin was administered at the beginning of labor, when more than 10 piglets still remained to be born.…”
Section: Introductionmentioning
confidence: 99%
“…The overall duration of parturition was registered as the time elapsed (min) from the rupture of amniotic membrane to the expulsion of placenta. Stillbirths were classified a s type I or before parturition deaths and intra-partum or type I1 following criteria previously described by Mota-Rojas et al (2002;2005a;b).…”
Section: Methodsmentioning
confidence: 99%